Linking Clinical Presentation with Coronary Anatomy: A Study of Angina Severity and Its Relationship with Angiographic Findings in Coronary Artery Disease : Linking Clinical Presentation with Coronary Anatomy: Angina Severity and CAD - Ullah, Haseeb; Iqbal, Muhammad Asif; Khan, Shahzeb; Khan, Nida; Ullah, Sana (Pakistan Journal of Health Sciences, 2026)
No intensive studies have been conducted locally or even in broader regions of the country, which results in a crucial knowledge gap in the establishment of the relationship between the severity of angina and the angiographic findings in patients with coronary artery disease (CAD). Objectives: To determine the correlation of angina severity with angiographic findings in patients diagnosed with coronary artery disease. Methods: This cross-sectional study was carried out at the Department of Cardiology, Lady Reading Hospital, Peshawar. Male and female patients of age 30 to 70 years diagnosed with coronary artery disease were evaluated for angina severity in comparison to angiographic findings. Results: Among 304 patients, angina severity demonstrated a strong positive correlation with angiographic findings (ρ = 0.875, p<0.001). Diabetic patients with severe angina had a higher proportion of high angiographic burden (36.8%) compared to non-diabetics (10.2%), while patients with family history of CAD showed a strong correlation (ρ = 0.886) and relatively weak correlation with Type C complex lesions (ρ = 0.706). Conclusions: A strong positive correlation was observed between angina severity and angiographic CAD burden, though this relationship was modified by diabetes, family history, and lesion complexity.